Gillet and Germain Hardouyn's print-assisted paintings prints as underdrawings in sixteenth-century French books of hours - Warren, Maureen (2021)
This chapter discusses the necessity of distinguishing between painted prints and print-assisted paintings. While a firm distinction between print and painting can be difficult to delineate, simply designating everything that blurs media boundaries a "hybrid" will flatten the nuances of both production and reception. The chapter provides short overview of both books of hours and the Hardouyn brothers. Afterword, the Hardouyn’s octavo metalcut of the Death of the Virgin, which was commissioned from the workshop of Jean Pichore, serves as a case study. Five overpainted impressions of this print are considered in chronological order, demonstrating some of the ways that individual painters elaborated upon the printed design to produce unique miniatures for the Hardouyns. Finally, the chapter explores the theory that the metalcut was intended to function as a printed underdrawing, arguing that the prints in Hardouyn Horae offer scholars a new method of studying both reproductive printmaking (broadly defined) and the role of underdrawing in Renaissance painting ateliers.
Keywords: Hardouyn, Germain; Pichore, Jean; Hardouyn, Gilles -- 1455-1529; Geschichte 1524; Vorzeichnung; Druckgrafik; Metallschnitt; Malerei; Stundenbuch